Synthesis of 1,1-bis-{2-Hydroxy-3-[1´ -Phenyl/H-5´ -Aryl-Pyrazolin-3´ -yl] -5-Methyl Phenyl} Methanes - P. GANORKAR, RAJESH; JAMODE, V.S. (Asian Journal of Chemistry, 2010)
Some new 1,1-bis-{ 2-hydroxy-3-[1' -phenyl/H-5'-aryl-pyrazolin- 3'-yl]-5-methyl phenyl} methanes (7a-h and 8a-h) have been synthesized by the action of 1,1-bis-{2-hydroxy-3-(3-aryl-prop- 2-en-1-one)-5-metbyl phenyl} methanes (5a-h) with phenyl hydrazine hydrochloride and hydrazine hydrate in pyridine medium.